2016
DOI: 10.1097/nmd.0000000000000518
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intensive Short-Term Dynamic Psychotherapy on Depressive Symptoms and Executive Functioning in Major Depression

Abstract: This study examined the efficacy of intensive short-term dynamic psychotherapy (ISTDP) on depressive symptoms and executive functioning in patients with major depression. We examined pretest, posttest, and follow-up depression scores as well as pretest-posttest executive functioning scores between 16 participants receiving ISTDP and 16 allocated to wait-list control. Participants in each group were matched according to age, sex, and educational level. Mixed-models analyses demonstrated significant interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Twenty percent of new presentations in primary care and 20–40% of medical outpatient referrals [ 3 , 4 ] present with high rates of somatization into bodily systems including the respiratory, cardiovascular, gastrointestinal, musculoskeletal, neurological and dermatological systems. The health and well-being of patients with these symptoms suffer to a greater extent due to related destructive health behaviors (e.g., smoking, poor diet, patterns of self-neglect, poor medication compliance), leading to disability and ultimately higher overall mortality [ 5 , 6 , 7 ]. This contributes to enormous healthcare costs, long waitlists and patient/clinician frustration [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Twenty percent of new presentations in primary care and 20–40% of medical outpatient referrals [ 3 , 4 ] present with high rates of somatization into bodily systems including the respiratory, cardiovascular, gastrointestinal, musculoskeletal, neurological and dermatological systems. The health and well-being of patients with these symptoms suffer to a greater extent due to related destructive health behaviors (e.g., smoking, poor diet, patterns of self-neglect, poor medication compliance), leading to disability and ultimately higher overall mortality [ 5 , 6 , 7 ]. This contributes to enormous healthcare costs, long waitlists and patient/clinician frustration [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main therapeutic interventions, which aim to unlock the unconscious, include confrontation, clarification, challenge to resistance, head on collision, facilitation of emotional experiences and recapitulation [10,[15][16][17][18][19][20]. The basis of ISTDP is resistance, transference and unconscious therapeutic alliance [10,[19][20][21][22][23], allowing this technique to be considered as an effective psychodynamic therapy, mainly by studies that cover follow-up interviews and post-treatment assessment measures [18,24,25].…”
Section: Dynamic Psychotherapymentioning
confidence: 99%
“…The literature indicates that interest in ISTDP is increasing. According to a study by Ajilchi, Nejati, Town, Wilson and Abbass (2016), patients with depression who were treated with ISTDP had decreased levels of depressive symptoms at end of treatment and at 12-months follow-up. Their executive functions also increased (Ajilchi et al, 2016).…”
mentioning
confidence: 99%
“…According to a study by Ajilchi, Nejati, Town, Wilson and Abbass (2016), patients with depression who were treated with ISTDP had decreased levels of depressive symptoms at end of treatment and at 12-months follow-up. Their executive functions also increased (Ajilchi et al, 2016). Randomized controlled trials concerning depression showed that ISTDP was connected to partial or complete remission 6 months after treatment, and also to increased socialcognitive capacity (Ajilchi, Kisely, Nejati, & Frederickson, 2018;Town et al, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation